Pathogenesis of the formation of erosive and ulcerative lesions of the duodenal bulb mucosa in smoking patients with chronic non-atrophic gastritis in the absence of active forms of hp infection - Avramenko, A.; Magdenko, A.; Dubinets, T.; Vasyuk, V.; Makarova, G. (Journal of Education, Health and Sport, 2026)
A pathogenetic explanation for the development of erosive and ulcerative lesions of the duodenal bulb was provided in 19 smoking patients with chronic non-atrophic gastritis. Three patients had previously suffered from peptic ulcer disease, and 10 patients had confirmed chronic non-atrophic gastritis with high levels of Helicobacter pylori infection, for which they had undergone anti-Helicobacter therapy. Over the past 2-3 years, due to military conflict in Ukraine, the patients had increased their daily cigarette intake (from 0.5-1 pack to 1.5-2 packs). When conducting an examination using two different methods (urease test and microscopy of stained smears-prints), an active form of HP infection was not detected, however, when conducting a breath test, a high increase in exhaled ammonia was obtained (the average level was 17.33 ± 0.42 mm), the source of which was smoking and which became the basis for the formation of erosive-ulcerative bulbitis.